Introduction to the Mathematical Theory of Control Processes: Nonlinear Processes - Bellman, Richard (New York: Academic Press, 1971)
The order of presentation in this volume is the reverse of the order in volume 1 where the calculus of variations was treated first. There the motivation was that a simple rigorous account could easily be given and that this approach could in turn be used to provide a rigorous derivation of the fundamental Riccati equation of dynamic programming.
Includes bibliographical references and index.
ne 26/03/2018
Loans
Keywords: Control Theory